Dialogue on Organization and Knowledge - Grandori, Anna; Kogut, Bruce (Organization Science, 2002)
Preface In lieu of writing an introduction that runs the risk of adding more smoke than fire, the guest editors elected to engage in a dialogue with one another. Its purpose is to give readers a sense of the thinking behind the special issue, of the debates that ensued, and of the possible directions for further work. We met for lunch in a cafe-bar in Greenwich Village in April 2001 to discuss the special issues introduction. Through a series of exchanges, the discussion emerged. What follows is a dialogue about Knowledge, Knowing, and Organizations.